The creation of high resolution bathymetry grids for Christmas Island - Mleczko, Richard; Geoscience Australia (Canberra : Geoscience Australia, 2010)
"Christmas Island is located approximately 2,600 North West of Perth. Bathymetry data are required in this area to help identify major seabed processes and habitats. The data are also required to enable modelling of tsunami as they interact with the shelf around the island and the coast. This report describes the methodology employed in creating detailed bathymetry data grids of the Christmas Island region. It covers data collection, quality control and gridding. Descriptions are provided of each dataset employed, the methods used to integrate the different datasets and the attributes of the new bathymetric models. Five new bathymetry grids are presented, including grids that integrate bathymetry with the island's topography."--Executive summary (p. 1)
4. Data processing. Swath processing. Singlebean processing. Chart data -- 5. Analysis and QC of bathymetric data. Fledermaus. ArcMap. Procedure -- 6. Gridding. Preliminary considerations. Gridding process. Christmas Island regional 250 m grid. Christmas Island 100 m grid. Christmas Island 50 m grid. Christmas Island bays gridded at 10 metres -- 7. Final grids -- Bibliography --Appendix. ANZLIC metadata record.
Geocat no.: 70652.
Bibliography: p. 37-38.
Also available online from the Geoscience Australia website at: www.ga.gov.au (Viewed 14 July 2011)
Keywords: Submarine topography -- Christmas Island (Indian Ocean) -- Mathematical models; Christmas Island (Indian Ocean) -- Bathymetric maps; Australian